Behavioral interactions between terrestrial salamanders and spiders: competition or intraguild predation?. Issue 4 (4th July 2018) - Hickerson, Cari-Ann M.; Anthony, Carl D.; Figura, Anna M.
Abstract : Several studies suggest that small terrestrial salamanders are important regulators of leaf litter arthropod communities, and likely contribute to ecosystem processes such as decomposition and nutrient cycling. Despite the recognition that salamanders have the potential to strongly affect ecosystem function through both direct and indirect pathways, little is known regarding the nature of interactions between small vertebrates and the large, predatory arthropods with which they share both microhabitat and prey. Our study was designed to explore interactions between Eastern Red-backed Salamanders, Plethodon cinereus, and spiders in the genus Wadotes in an eastern North American temperate forest ecosystem. We were particularly interested in teasing apart behaviors such as territoriality and intraguild predation in an attempt to determine specifically which interaction is most likely responsible for the observed negative relationship between salamander and spider abundance at our field site. Field data indicate that P. cinereus and large syntopic spiders exhibit negative spatial associations in the microhabitat beneath cover objects, a possible indication of interspecific territoriality. In our laboratory experiments, resident salamanders displayed agonistic postures similarly toward both intruding conspecifics and spiders, suggesting that salamanders may perceive large intruding spiders as competitors. Finally, we observed no injuries to individual P. cinereus or adult spiders even though occasional chases and bites by both were recorded during the behavioral trials. We found no evidence that adults or juveniles of P. cinereus were envenomated by adult Wadotes spp., and there were no instances of intraguild predation in this study. Multiple lines of evidence from this study, and others, suggest that the primary interaction between individuals of P. cinereus and large spiders is competitive in nature rather than predatory. We suggest that the cost associated with intraguild predation on salamanders with noxious skin secretions may preclude them from being preyed upon by spiders.